Economic Analysis, Effectiveness and Efficiency of Budget Use in Infrastructure Projects - sholeha; Rahma, Filasti; Saputri, Andriani (International Journal of Multidisciplinary Learners, 2025)
This research aims to analyze and measure the economy, effectiveness and efficiency of budget use in infrastructure projects. The population in this research is budget realization reports. The sampling technique used in this research is the 2018-2022 Budget Realization Report. The research method is a quantitative descriptive type that uses primary data and secondary data. The data collection techniques used in this research are documentation and interview techniques. The data analysis technique uses ratio analysis. The economic level of use of the South Buton Regency Public Works and Spatial Planning Department's budget for 2018-2022 is included in the very economical category. This shows that the Public Works and Spatial Planning Department of South Buton Regency, in achieving budget realization, has used its budget well in the sense of being able to save costs. The level of effectiveness in using the South Buton Regency Public Works and Spatial Planning Department's budget for 2018-2022 is in the quite effective category. This shows that the Public Works and Spatial Planning Department of South Buton Regency, in achieving the realization of the expenditure budget, has achieved enough to realize it maximally from the budget that has been set to achieve the target or organization. The level of efficiency in using the South Buton Regency Public Works and Spatial Planning Department's budget for 2018-2022 is in the very efficient category. This shows that the Buton Regency Public Works and Spatial Planning Service.